Alzheimer's disease : life course perspectives on risk reduction - Borenstein, Amy R.; Mortimer, James A. (ClinicalKey., 2016)
Alzheimer's Disease: Lifecourse Perspectives on Risk Reduction summarizes the growing body of knowledge on the distribution and causes of Alzheimer's disease (AD) in human populations, providing the reader with knowledge on how we define the disease and what its risk and protective factors are in the context of a life-course approach. At the conclusion of the book, the reader will understand why Alzheimer's disease likely begins at conception, then progresses through early-life and adult risk factors that ultimately impact the balance between pathologic insults in the brain and the ability of the brain to modify disease symptoms. In contrast to edited volumes that may have little cohesion, this book focuses on an integrated life-course approach to the epidemiology of dementia, in particular, Alzheimer's disease.